Design and development of wideband 3dB/90 couper using multiple-rows vias substrate integrated waveguide (SIW) technique - Nurehansafwanah Khalid author (School of Computer and Communication Engineering, 2018)
The scope of this project is to design and develop coupler with 3dB/90o Substrate Integrated Waveguide (SIW) techniques for microwave applications. To validate the proposed SIW techniques on coupler designs. The design is investigated and implemented at two different high frequency range which is at Ku-Band and K-Band. In this research thesis, all designed couplers are implemented on Roger 4003C dielectric substrate. An analytical SIW calculation is done to verify the initial and optimized dimension of the coupler. In order to match between the SIW transitions to microstrip transition, tapered transition is applied. The simulation and optimization are carried out using Computer Simulation Tools (CST) Software. The simulated results of S-parameters such as return loss, insertion loss, transmission coefficients and phase difference between outputs are obtained. All the prototypes of coupler are implemented using Printed Circuit Board (PCB), CNC machine and Bungard drill holes. The measured couplers (experimental) is validated using Vector Network Analyzer (VNA).